2006
DOI: 10.1007/s00280-006-0337-z
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of trastuzumab in combination with chemotherapy in human gastric cancer xenograft models

Abstract: The antitumor activity of trastuzumab observed in human gastric cancer models warrants consideration of its use in clinical treatment regimens for human gastric cancer as a single agent or a combination drug with various chemotherapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(116 citation statements)
references
References 17 publications
3
110
0
3
Order By: Relevance
“…12,48,49,52 For HER2 amplification, NCI-N87 cells were used as positive control and MKN-45 and AGS cells were used as negative control. 53,54 In a pilot study of MET, MST1R and HER2 FISH in human GEC, tissue sections from three patients mounted on conventional slides were processed according to Vysis/Abbott Molecular pretreatment protocol for formalin-fixed paraffin-embedded specimens adjusted for gastric epithelia. In all FISH experiments, the hybridization procedure and post-hybridization washes were done as described by Vysis/Abbott Molecular.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,48,49,52 For HER2 amplification, NCI-N87 cells were used as positive control and MKN-45 and AGS cells were used as negative control. 53,54 In a pilot study of MET, MST1R and HER2 FISH in human GEC, tissue sections from three patients mounted on conventional slides were processed according to Vysis/Abbott Molecular pretreatment protocol for formalin-fixed paraffin-embedded specimens adjusted for gastric epithelia. In all FISH experiments, the hybridization procedure and post-hybridization washes were done as described by Vysis/Abbott Molecular.…”
Section: Methodsmentioning
confidence: 99%
“…To verify the efficiency of homebrewed MET and MST1R probes in formalin fixed and paraffin embedded (FFPE) human gastric cancer sections and to compare GCN FISH results with those of quantitative polymerase chain reaction (qPCR) and array comparative genomic hybridization (aCGH) assays, we performed a pilot FISH study of three randomly selected gastric cancer cases from the cohort of tumors with defined status of GCN detected by these two methods. Results are presented in 53,54 (Fig. 6E).…”
Section: Alterations In Mst1r (Ron) Gene By Fishmentioning
confidence: 99%
“…NCI-N87 and SNU216 are cell lines in which HER2 is amplified. The copy number ratio of the HER2 gene determined by FISH analysis was found to be 4.34 for SNU216 cells and 8.4 for N87 cells (14,15). Upon receipt, all cell lines were stored in liquid nitrogen, and passaged for less than 6 months before use for this study.…”
Section: Cell Lines and Culturingmentioning
confidence: 99%
“…It has been reported that trastuzumab has significant antitumor activity related to Her 2/neu expression in gastric cancer cells and xenograft models (4)(5)(6). This finding has prompted investigation of the potential clinical benefits of trastuzumab in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%